A web-based personally controlled health management system increases sexually transmitted infection screening rates in young people: a randomized controlled trial. (15th March 2015) - Mortimer, Nathan J; Rhee, Joel; Guy, Rebecca; Hayen, Andrew; Lau, Annie Y S
Abstract: Objective To determine if a web-based personally controlled health management system (PCHMS) could increase the uptake of sexually transmitted infections (STI) screening among a young university population. Methods A non-blinded parallel-group randomized controlled trial was conducted. Participants aged 18–29 years were recruited from a university environment between April and August 2013, and randomized 1:1 to either the intervention group (immediate online PCHMS access) or control group (no PCHMS access). The study outcome was self-reported STI testing, measured by an online follow-up survey in October 2013. Results Of the 369 participants allocated to the PCHMS, 150 completed the follow-up survey, and of the 378 in the control group, 225 completed the follow-up survey. The proportion of the PCHMS group who underwent an STI test during the study period was 15.3% (23/150) compared with 7.6% (17/225) in the control group ( P = .017). The difference in STI testing rates within the subgroup of sexually active participants (20.4% (23/113) of the PCHMS group compared with 9.6% (15/157) of the control group) was significantly higher ( P = .027) than among non-sexually active participants. Discussion Access to the PCHMS was associated with a significant increase in participants undergoing STI testing. This is also the first study to demonstrate efficacy of a PCHMS targeting a health concern where susceptibility is generally perceived as low and the majority of infections are asymptomatic. Conclusion PCHMS interventions may provide an effective means of increasing the demand for STI testing which, combined with increased opportunistic testing by clinicians, could reduce the high and sustained rates of STIs in young people.